The Kingfisher science encyclopedia - Taylor, Charles (Kingfisher Publications, London, 2000)
Opslagsværk ordnet i hovedgrupperne: Plannet Earth, Living things, Human biology, Chemistry and the elements, Materials and technology, Light and energy, Forces and movement, Electricity and electronics, Space and time, Conservation and the environment